THE EFFECTIVENESS OF COOPERATIVE INTEGRATED READING AND COMPOSITION (CIRC) TECHNIQUE IN TEACHING READING COMPREHENSION ON HORTATORY EXPOSITION TEXT - Jauharotun Nafisah (Edulingua: Jurnal Linguistiks Terapan dan Pendidikan Bahasa Inggris, 2018)
The main purpose of English learning is to develop four skills of the students. Unfortunately, the students got difficulties in reading. The reading comprehension on Hortatory Exposition text of the eleventh grade students of MA Darul Hikmah Menganti Kedung Jepara is low. The subject of this research were 68 students. The objective of this research is to know whether there is a significant difference between the reading comprehension on Hortatory Exposition text of the eleventh-grade students of MA Darul Hikmah Menganti taught by using Cooperative Integrated Reading and Composition (CIRC) Technique and those who are taught by using Three Phase Technique in academic year 2017/2018. This research is a true experimental research which takes the eleventh grade students of MA Darul Hikmah Menganti Kedung Jepara as the population. The instrument of the research was test. The data were gathered through only post-test.  The result of the research showed that the student’s reading comprehension on Hortatory exposition text of the eleventh grade students of MA Darul Hikmah by using CIRC Technique was more sigificant difference. The post-test score of the experimental group (82.4) is higher than the control group (71.4). from the result of statistic calculation, it was obtained that the value of t-observation () is 5.39 and degree of freedom (df) is 66. In the table of significance 5%, the value of degree of significance is 1.99. comparing those values, the result is 5.39 > 1.99 which means that t-observation () score was higher than t-table () score. In the other words, the Alternative Hypothesis (Ha) is accepted and the Null Hypothesis (Ho) is rejected. Therefore, teaching reading comprehension on hortatory exposition text by using CIRC technique is effective than Three Phase technique.